Acromegaly in a patient with a pulmonary neuroendocrine tumor: case report and review of current literature. (December 2016) - Krug, Sebastian; Boch, Michael; Rexin, Peter; Pfestroff, Andreas; Gress, Thomas; Michl, Patrick; Rinke, Anja
Abstract Background Pulmonary neuroendocrine tumors (NET) form a heterogeneous group of rare diseases. In these tumors, paraneoplastic syndromes have been described to drive the course of the disease, among them acromegaly induced by paraneoplastic secretion of growth hormone-releasing hormone (GHRH). Case presentation We report the case of a 43 years old patient initially diagnosed with acromegaly accompanied by weight gain and acral enlargement. Subsequently, further diagnostic work-up identified a solitary pulmonary neuroendocrine tumor (NET). Laboratory tests revealed markedly increased growth hormone (GH) and insulin-like growth factor 1 (IGF-1) without GHRH elevation in the absence of pituitary pathologies confirming the paraneoplastic origin of clinical presentation with acromegaly. Curative surgery was performed leading to normalization of the elevated hormone levels and improvement of the clinical symptoms. Immunohistochemically, a typical carcinoid (TC) was seen with low proliferation index and abundant IGF-1 expression. Conclusions The association of acromegaly and pulmonary NET has only rarely been reported. We present an individual case of paraneoplastic GH- and IGF-1 secretion in a patient with pulmonary NET. Based on their rarity, the knowledge of paraneoplastic syndromes occurring in patients with pulmonary NET such as acromegaly due to paraneoplastic GH- and IGF-1 secretion is mandatory to adequately diagnose and treat these patients.